2020
DOI: 10.1002/brb3.1989
|View full text |Cite
|
Sign up to set email alerts
|

Physiological measurement of emotion from infancy to preschool: A systematic review and meta‐analysis

Abstract: Introduction Emotion regulation, the ability to regulate emotional responses to environmental stimuli, develops in the first years of life and plays an important role in the development of personality, social competence, and behavior. Substantial literature suggests a relationship between emotion regulation and cardiac physiology; specifically, heart rate changes in response to positive or negative emotion‐eliciting stimuli. Method This systematic review and meta‐analysis provide an in‐depth examination of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 136 publications
(140 reference statements)
1
16
0
Order By: Relevance
“…These finding are important because they suggest our EE Task shows convergent validity with parent-reported temperament, specifically the affective responses during negative tasks for mask 1, mask 2, hair brushing, and face washing and gaze durations for baseline 1). These results are in line with a recent review by Sacrey et al [ 55 ], which reviewed physiological and affective responses during emotionally salient tasks and found that the overwhelming majority of studies used negatively salient tasks to elicit responses. That there were relationships between EE Task and the IBQ-R at 18 months for the combined and IL group, but not the LL group may be due to the age parameters of the IBQ-R.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These finding are important because they suggest our EE Task shows convergent validity with parent-reported temperament, specifically the affective responses during negative tasks for mask 1, mask 2, hair brushing, and face washing and gaze durations for baseline 1). These results are in line with a recent review by Sacrey et al [ 55 ], which reviewed physiological and affective responses during emotionally salient tasks and found that the overwhelming majority of studies used negatively salient tasks to elicit responses. That there were relationships between EE Task and the IBQ-R at 18 months for the combined and IL group, but not the LL group may be due to the age parameters of the IBQ-R.…”
Section: Discussionsupporting
confidence: 91%
“…A critical consideration when assessing ER is to determine whether the tasks are producing the expected result (i.e., the putatively negative tasks elicit negative responses [ 55 ]). The tasks used in this study were adapted from the Lab-TAB [ 24 ] and were designed to probe-specific emotions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that the analysis used here could be applied to the behavior of at-risk human infants in the way that it was applied here to infant rats. The development of behavior of human infants is also organized, and this organization is widely used to assess the attainment of developmental milestones ( Harris and Heriza, 1987 ; Sacrey et al, 2020 ). The assessment of milestones, however, depends upon the accuracy of the rating tool, the expertise of the rater, and it can be confounded by the normal developmental variability of infants.…”
Section: Discussionmentioning
confidence: 99%